UNIMAS TESL undergraduates' preferences in choosing group members for group assignment - Cordelia Lonie, Kaniasen (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Tertiary institutions often implement group work that can help to make the learning environment to be more learner-centered. Group work provides the opportunities for learners to be more active in learning and to share their knowledge, and to develop their problem solving skills This study investigates the different preferences among 101 UNIMAS TESL year 3 and year 4 undergraduates in choosing their group members for group assignments and the reasons for their choice through survey case study. The instruments used for the data collection were questionnaire and interview. 10 participants from TESL year 3 and year 4 were selected for the interview session. Results showed that most of the UNIMAS TESL undergraduates preferred to choose their own group members when doing group assignments. In contrast, to be grouped randomly was the least preferred grouping preference. In addition, the results also showed that the reasons for the students' most preferred grouping preferences were due to the factors such as; fun, comfortable, easy to work with, ease in communication, fair, save time, giving advantages to the lower ability students, and multicultural. The findings of the study can serve as one of the basis reference for TESL lecturers to be aware of what and how the students actually prefer to be grouped